SOSIALISASI PENGELOLAAN SAMPAH ORGANIK BERBASIS SUMBER DENGAN PEMBUATAN “TEBE MODERN” PADA PESERTA DIDIK SMP DHARMA PRAJA BADUNG - Suanda, I Wayan; Rusmayanthi, Kadek Intan; Sumada, I Made; Alit, Dewa Made (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2024)
The management of waste produced by community households is not yet optimal, especially the handling of organic waste. To reduce the negative impact of organic waste whose management is not optimal, community service is carried out in the form of education and socialization of the application of organic waste processing by creating "Tebe Modern". This service activity is carried out using a descriptive evaluative method which is carried out by describing and analyzing the situation of the land used and maximized by socialization activities about how to process source-based waste by making "Tebe Modern". The results of this community service activity produced very good results, marked by high appreciation and enthusiasm from students, related agencies and community leaders.